2018
DOI: 10.1016/j.molmet.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The adaptor protein PID1 regulates receptor-dependent endocytosis of postprandial triglyceride-rich lipoproteins

Abstract: ObjectiveInsulin resistance is associated with impaired receptor dependent hepatic uptake of triglyceride-rich lipoproteins (TRL), promoting hypertriglyceridemia and atherosclerosis. Next to low-density lipoprotein (LDL) receptor (LDLR) and syndecan-1, the LDLR-related protein 1 (LRP1) stimulated by insulin action contributes to the rapid clearance of TRL in the postprandial state. Here, we investigated the hypothesis that the adaptor protein phosphotyrosine interacting domain-containing protein 1 (PID1) regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
(53 reference statements)
3
16
0
Order By: Relevance
“…Substantive SNPs introduced by imputation reached the suggestive level associated with cholesterol. SNPs rs17578959 and rs28845526 were located in the PID1 gene, which served as the regulator of the LDLR-related protein 1 ( LRP1 ) function and controlled the processing of postprandial lipoproteins ( 68 ). Solute Carrier Family 13 Member 1 ( SLC13A1 ) gene can regulate the cholesterol level by participating in transport of glucose and other sugars, bile salts and organic acids, metal ions and amine compounds pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Substantive SNPs introduced by imputation reached the suggestive level associated with cholesterol. SNPs rs17578959 and rs28845526 were located in the PID1 gene, which served as the regulator of the LDLR-related protein 1 ( LRP1 ) function and controlled the processing of postprandial lipoproteins ( 68 ). Solute Carrier Family 13 Member 1 ( SLC13A1 ) gene can regulate the cholesterol level by participating in transport of glucose and other sugars, bile salts and organic acids, metal ions and amine compounds pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to see how cargo specificity in the retrieving pathway is achieved and how this is physiologically regulated. Recently, an elegant study has suggested that the adaptor protein PID1, which regulates whole body glucose homeostasis, is an insulin‐dependent molecular switch that regulates the cellular distribution of another cholesterol transporter, LRP1 (low density lipoprotein particle related protein 1), and functions in the postprandial state by controlling SNX17 binding to LRP1 . Interestingly, the CCC complex is also required for LRP1 trafficking to the plasma membrane, suggesting that this complex could mediate the insulin‐dependent regulation of LRP1 trafficking via PID1 .…”
Section: Regulation Of Glucose and Lipid Metabolism Through The Endosmentioning
confidence: 99%
“…LRP1 belongs to the LDL receptor (LDLR) family and involves in various biological processes, such as lipid metabolism, degradation of proteases, tissue invasion, and cell growth or differentiation . Recent study has found that PID1 lowers plasma levels of pro‐atherogenic triglyceride‐rich lipoproteins (TRL) remnants by stimulating endocytic function of both LRP1 and LDLR in the liver . Thus we hypothesized that PID1 might play a role in lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%